Effectiveness of Assertiveness Training on Assertion and Social Problem Solving of Male Students Who are Victims of Bullying - Mohammad Mohammadi (Alzahra University, 2021)
The aim of this study was to investigate the effectiveness of assertiveness training on assertion and social problem solving of male victims of bullying in junior high school. The research method was quasi-experimental with pre-test, post-test with control group. The statistical population of the study consisted of all male high school students in Marivan city, who were studying in the 2018-2019 academic year. Using cluster random sampling method, 60 students were selected and randomly assigned to experimental (30) and control (30) groups. The participants of the experimental group were trained in groups for six weeks and two sessions per week (12 sessions in total). The experimental group received assertiveness training intervention as a group for six weeks, but the control group did not receive assertiveness training during the study. Research tools included questionnaires of bullying, assertiveness and social problem solving. Data were analyzed using analysis of covariance. The results showed that assertiveness training had a significant effect on the level of assertion but no effect on social problem solving. According to the findings of the present study, it can be concluded that assertiveness skills training can be used as an effective method to increase the assertion of students who are victims of bullying.